The importance of being a myoepithelial cell - Deugnier, Marie-Ange (BioMed Central, 2002)
The mammary myoepithelial cell was named the 'Cinderella of mammary cell biology' in light of the earlier focus on the luminal cell. Mammary myoepithelial cells have recently been described as 'natural tumour suppressors'. We now need to understand more about their origin and to reconsider their place in the complex process of mammary morphogenesis. In the present review, we discuss the lineage segregation of mammary myoepithelial cells and their functions in mammary gland development. These functions include their effects on luminal cell growth and differentiation, their key role in the establishment of the polarised mammary epithelial bilayer and the control of stromal invasion in breast cancer.